The Evaluation of Mergers on the Financial Performance of PT Bank Syariah Indonesia - Maya Puspita Sari (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2022)
To increase the market share and strengthen the capital of Islamic banking in Indonesia as well as to expand their business activities, the government expanded Islamic banks externally through the merger of three state-owned Islamic banks to become Bank Syariah Indonesia. The method used in this research is descriptive quantitative where this study analyzes the financial performance of Islamic Banks forming Bank Syariah Indonesia which consists of 3 (three) Islamic banks namely PT Bank Syariah Mandiri, PT Bank BRI Syariah, and PT Bank BNI Syariah during the research period 2019-2022, by comparing 2 periods before and 2 periods after the merger. The results of the Paired sample t-test showed that there were differences for the 5 (five) financial ratios of the 8 (eight) financial ratios studied between before and after the merger in the observation period. These results indicate that the merger provided a significant improvement in the financial performance of PT Bank Syariah Indonesia.